HOMA-beta independently predicts survival in patients with advanced cancer on treatment with immune checkpoint inhibitors - Watanabe, Mayu; Eguchi, Jun; Takamoto, Atsushi; Kanzaki, Hiromitsu; Noda, Yohei; Kagawa, Syunsuke; Wada, Jun (Frontiers in Endocrinology, 2024)
Although immune checkpoint inhibitors (ICIs) are effective cancer drugs, ICI-induced diabetes is a rare but a life-threatening adverse event for patients. The deleterious action of ICI on pancreatic betacell function is a concern. However, the influence of ICI on insulin synthesis and secretion in patients with cancer without diabetes remains unknown.This study included 87 patients diagnosed with advanced cancer. Glucose metabolism markers (HbA1c, HOMA-IR) and indicators of insulin secretory capacity (HOMA-beta, C-peptide) were prospectively evaluated in patients with ICI-treated cancers to determine their association with cancer prognosis.Patients with overall survival (OS) ≥ 7 months had substantially higher HOMA-beta levels at baseline (p=0.008) and 1 month after ICI administration (p=0.006) compared to those with OS <7 months. The median OS was significantly longer in patients with 37 events) than in those with HOMA-beta < 64.24 (5 months, 95%CI: 3.280-6.720, 50 events) (p=0.013). Further, the median progression-free survival (PFS) was significantly longer in patients with HOMA-beta ≥ 66.43 (4 months, 95%CI: 3.073-4.927, 33 events) than in those with HOMA-beta < 66.43 (2 months, 95%CI: 1.410-2.590, 54 events) (p=0.025). Additionally, multivariable logistic regression analysis revealed that a HOMA-beta value ≥ 64.24 independently predicted longer OS in ICI-treated patients.